Adaptación del adolescente al proceso de maternidad. abril-agosto 2018. - Taipe Coque, Gladys Alicia (2018)
The care of the nursing professional to support the process of adaptation to the maternity of the adolescent mother requires a focus on three fundamental aspects: affective bond, care of the mother and care skills for the newborn. The present bibliographical review was made through critical reading of publications in: Scielo, PubMed, LILACS from 2011 to 2018 with the objective of answering the questions: What are the adaptation problems in the maternity process of adolescents? What are the actions of nursing according to the problems presented in adolescents in the maternity process? According to the review of scientific literature, physiological anemia is the most frequent physiological change in adolescent mothers; among the psychological changes highlight anxiety, depression, loneliness and frustration; the main socioeconomic problems are school dropout, economic instability and the loss of the life project. The main aspects to be included in the nursing care of the adolescent mother to support adaptation to the maternity process are the affective bond, the maternal state oriented to self-care and the strengthening of the skills for the care of the newborn.